An IMP interaction approach to modelling business-to-business professional service quality: the case of Hong Kong consulting engineering service - Woo, Ka-shing (2001)
In the domain of services marketing, the most researched area is in service quality. Since the pioneering stage of service quality research in the early 1980s, most of the studies have been conducted in the context of consumer services and consumer professional services. The purpose of this study is to bridge the gap in the existing literature to measure service quality of a particular business-to-business professional service industry (i.e., Hong Kong consulting engineering industry).